al-Mustalahat al-waqfiyah - Atiqi, Muḥammad Kull Ubayd Allah; Tuni, Izz al-Din.; Shuayb, Khalid (Kuwait : [Kuwait Awqaf Public Foundation], 2009)
Dictionary of waqf terminology.
Includes bibliographical references.
Keywords: Waqf -- Terminology